Checklists in pre‐hospital advanced airway management. Issue 1 (9th September 2019) - Klingberg, Cecilia; Kornhall, Daniel; Gryth, Dan; Krüger, Andreas J.; Lossius, Hans Morten; Gellerfors, Mikael
Abstract : Background: In pre‐hospital care, pre‐intubation checklists (PICL) are widely implemented as a safety measure and guidelines support their use. However, the true value of PICL among experienced airway providers is unknown. This study aims to explore possible benefits and disadvantages of PICL in the pre‐hospital setting. Methods: We performed a subgroup analysis of a prospective, observational, multicentre study on pre‐hospital advanced airway management in the Nordic countries between May 2015 and November 2016. The original trial was designed to investigate the success rates of pre‐hospital tracheal intubations and the incidence of complications. Our study limited inclusion to drug assisted intubations performed by anaesthesiologists. Intubation success rates and complication rates were plotted against checklist use. Results: We analyzed 588 pre‐hospital intubations for medical and traumatic emergencies. Overall, checklists were used in 60.5% of instances. Applying checklists was associated with increased success at first and second intubation attempts. There was no significant difference in the overall success rates (99.4% and 99.1%). Oesophageal misplacement was more common in the No‐PICL group (2.2% vs 0.3%) but otherwise the incidence of airway related complications did not differ between the groups. Scene time was significantly shorter in the No‐PICL group (23.6 vs 27.5 minutes). Conclusion: In this retrospective study, checklist use correlated with fewer attempts at intubation when securing the airway. Despite this, we found no association between checklist use and the overall TI success rate or the incidence of serious adverse events. Scene times were shorter without PICL.